2015
DOI: 10.1016/j.pharep.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of functional minor allele variants of drug metabolizing CYP2B6 and CYP2D6 genes in Roma population samples

Abstract: Our results demonstrate an increased minor allele frequency for CYP2B6 and CYP2D6 polymorphisms in Roma samples that implies clinical significance in this ethnic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
3
6
0
Order By: Relevance
“…This was significant difference compared with figure observed in Europe, America, and Middle East, where CYP2D6 ∗4 was reported with high frequency. [20,22,29,36] This result is in accordance with previous works, in which a gradual decrease of CYP2D6 ∗4 from Europe to Asia countries was reported. [41] Although CYP2D6 ∗36 frequency (0.37%) was shown significantly lower than that in Thailand (16.4%), [18] however, similar figures were reported in various populations in the world containing Chinese Han, Papua New Guineans, and South African.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was significant difference compared with figure observed in Europe, America, and Middle East, where CYP2D6 ∗4 was reported with high frequency. [20,22,29,36] This result is in accordance with previous works, in which a gradual decrease of CYP2D6 ∗4 from Europe to Asia countries was reported. [41] Although CYP2D6 ∗36 frequency (0.37%) was shown significantly lower than that in Thailand (16.4%), [18] however, similar figures were reported in various populations in the world containing Chinese Han, Papua New Guineans, and South African.…”
Section: Discussionsupporting
confidence: 92%
“…[15,16,40] Statistical analysis also demonstrated significant higher frequency of CYP2D6 ∗10 in Kinh Vietnamese compared with other worldwide regions except for Asian countries. [20,27,31,33,36] Our work further approved the high prevalence of CYP2D6 ∗10 retricted to Asian populations. Meanwhile, the nonfunction allele CYP2D6 ∗4 was very rare in our study subjects as well as in other Asian populations.…”
Section: Discussionsupporting
confidence: 58%
“…1,2 Of particular interest is the enzyme's role in the conversion of pain medications to active metabolites, namely morphine. [3][4][5] The highly polymorphic nature of CYP2D6 results in various metabolizer phenotypes (MP; poor (PM), intermediate (IM), extensive (EM) and ultra-rapid (UM)), [6][7][8] typically inferred from the diplotype of CYP2D6 star (*) alleles (a haplotype of one or more polymorphisms along the length of the gene), 9 that have been associated with lack of therapeutic response, idiosyncratic responses, or even death. [10][11][12] Comprehensive pharmacogenetic studies have shown that single-nucleotide polymorphisms (SNPs) in other opiate metabolism and pain relief pathway genes also confer variable degrees of enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic distinctiveness of the Roma population when considering pharmacogenes has been detected in various individual genes; in some of the CYP genes, [30][31][32] in SLCO1B1, 33 VKORC1, 34 PON1 and P2RY12 35 genes. In addition, it was recently confirmed in a comprehensive analysis of a set of 95 pharmacogenomically relevant polymorphic markers (from 31 core ADME genes) of drug response and adverse drug reactions in the Roma and twenty other, ethnically different populations from the 1000 Genomes database.…”
Section: Discussionmentioning
confidence: 99%